2022
DOI: 10.1039/d2ra05128a
|View full text |Cite
|
Sign up to set email alerts
|

A green fluorescence turn-off system for meclofenoxate determination by Cilefa Pink B dye

Abstract: The decoration of a facile switch-off fluorescent system utilizing a safe food dye (Cilefa Pink B) for meclofenoxate investigation through an electrostatic attachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…The greener analysis, the more valuable it is (given a high number). [ 42 ] This is because the procedure we created used methanol as a solvent, and no extraction, heating, or energy‐consuming processes were used per sample (less than 0.1 kW h). Using the eco‐scale, our designed approach scored 92, which indicated that our method was environmentally friendly [ 43 ] (Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…The greener analysis, the more valuable it is (given a high number). [ 42 ] This is because the procedure we created used methanol as a solvent, and no extraction, heating, or energy‐consuming processes were used per sample (less than 0.1 kW h). Using the eco‐scale, our designed approach scored 92, which indicated that our method was environmentally friendly [ 43 ] (Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…It was discovered that distilled water exhibited the greatest efficacy and was the most suitable diluent for diluting the reaction medium. The observed phenomenon could potentially be attributed to a higher dielectric constant (80.2) and a greater polarity index of the water compared to the other solvents employed in the study [54–57].…”
Section: Resultsmentioning
confidence: 99%
“…Biological and pharmaceutical analysts play a crucial role in protecting the environment and people from hazardous distribution media and organic residue [ 55 , 56 ]. The field of green analytical chemistry is in a state of continuous development and necessitates regular consideration.…”
Section: Resultsmentioning
confidence: 99%